State Universities as Centers for Dialogue Between Science, Religion and Culture - Abdul Latif Rahmat; Moh. Roqib (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
This research study was conducted to examine models of integration of science, religion and culture in State Universities in Indonesia, especially State Islamic Universities (UIN). This research uses the integrative literature review method, where researchers combine various articles, books and other literature regarding the integration model of science, religion and culture in state universities. The results of this study show that State Universities are part of educational institutions that can be used as a center for dialogue between science, religion and culture. This can be seen from several campuses that have their own models in integrating science, religion and culture in state universities. Such as UIN Syarif Hidayatulloh, UIN Sunan Ampel Surabaya, UIN Sunan Kalijaga, UIN Sumatera, UIN Maulana Malik Ibrahim.